Pecularities of the natural regenaration on the windthrow areas in the Carpathian national nature park - Lavnyy, Vasyl (Forestry, Forest, Paper and Woodworking Industry, 2024)
The paper provides a detailed characterization of natural regeneration on the windthrow areas in Carpathian National Nature Park. In general on investigated sample plots prevails good natural regeneration of trees. In the composition of understorey on all windthrow areas had spruce dominated and as admixture were silver fir and beech presented, thus it is the trend to natural regeneration of primar stands. It was also the composition, average height and canopy density of herbaceous cover on the investigated plots determined.